Anesthesia and Perioperative Care for Aortic Surgery - Subramaniam, Kathirvel; Park, Kyung W.; Subramaniam, Balachundhar (Springer New York : Imprint: Springer, 2011)
This is the first comprehensive reference on anesthesia and perioperative care for aortic surgery. Edited and written by leading experts in medicine, surgery, and anesthesia, it provides detailed descriptions of aortic surgery and anesthesia for specific aortic procedures, including ascending aorta, arch, descending aorta, endovascular surgery, trauma, and surgery for congenital aortic pathologies. The book devotes separate chapters to intraoperative echocardiography and cerebral monitoring, and because organ dysfunction is a major cause of mortality and morbidity after aortic surgery, it addresses spinal cord and renal protection. A final chapter covers postoperative care. Anesthesia and Perioperative Care for Aortic Surgery is a "must" for cardiac anesthesiologists, cardiac surgeons, intensivists, nurse anesthetists, and residents and fellows involved in this growing area.